Vision and abstraction: an empirical refutation of Nico Orlandi's non-cognitivism. (2nd April 2016) - Mole, Christopher; Zhao, Jiaying
Abstract: This article argues against the non-cognitivist theory of vision that has been formulated in the work of Nico Orlandi. It shows that, if we understand 'representation' in the way Orlandi recommends, then the visual system's response to abstract regularities must involve the formation of representations. Recent experiments show that those representations must be used by the visual system in the production of visual experiences. Their effects cannot be explained by taking them to be non-visual effects involving attention or memory. This contradicts Orlandi's version of the non-cognitivist hypothesis, but does so while vindicating her methodological position.